The effect of giving pumpkin pudding (curcubita moschata) on sleep quality postpartum - Sandy Nurlaela Rachman; Lina Mardianti; Ilvika Mei Alkafili (Institute of Computer Science (IOCS), 2026)
The postpartum period is a period of recovery of reproductive organs which is a period vulnerable to discomfort after childbirth, one of which is sleep disorders. In Indonesia, around 53.9% of postpartum mothers experience sleep disorders that can reduce the quality of life and increase the risk of fatigue or postpartum blues (Rofiasari, 2024), so there is a need for safe intervention efforts to improve sleep quality, such as non-pharmacological interventions, namely pumpkin (Cucurbita moschata) where its content is important in sleep regulation, so it has the potential to improve the quality of sleep of postpartum mothers (Ariani, 2023). The purpose of the study was to determine the effect of giving pumpkin pudding (Cucurbita moschata) to postpartum. This research method used a one-group pre-test and post-test design, with sample 44 participants using independent t-test analysis. The results showed that sleep quality was categorized low in 39 participants (88.6%) before the pre-test and good in 38 participants (86.4%) after the intervention. There was also an effect of pumpkin (Curcubita moschata) pudding on sleep quality postpartum (p-value 0.000 <0.05). The conclusion of this study that pumpkin affects changes in sleep quality in postpartum. Therefore, it is necessary to prioritize rest and sleep quality through foods that support physical recovery and sleep regulation, such as pumpkin. This study recommends that social support and health education by healthcare professionals regarding good nutritional choices are needed to support postpartum adaptation.